Developing an Education & Integrated Critical Event Model (ICEM) Research Training by Using a Mentoring Strategy for Health College Lecturers - Mulastin, Mulastin; Samsudi, Samsudi; Rusdarti, Rusdarti (The Journal of Educational Development, 2016)
As part of the three functions of higher education, lecturers should be able to develop new findings through research activities and use them for teaching materialsals for their students. However, there are still lecturers who do not have adequate competence in carrying out research activities and publish their research findings in scientific journals. Therefore, a model for education and trainingICEM for lecturers of Health Colleges in Central Java is still needed. The model is combined with a tutorial strategy for all stages of research activities. This study is meant to develop a research education and training ICEM model combined with a mentoring strategy, including planning, implementation, and evaluation. After three states of preliminary study, development, and testing, the model is significantly effective and can be used as an alternative model for training research activities for lecturers of Health Colleges in Central Java.